Penguatan Manajemen Industri Berbasis Potensi Lokal untuk Pemberdayaan Ekonomi Masyarakat di Desa Bukit Hijau, Kecamatan Bulawa - Uloli, Hendra; Larosa, Esta; Pramudibyo, Sugeng; Rahmandan, Hafid (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The development of local potential–based economies in rural areas continues to face various challenges, particularly in business management and the utilization of digital marketing by MSME actors. This condition is also experienced by the community of Bukit Hijau Village, Bulawa District, which possesses potential marine-based processed products that have not yet been optimally managed. This community service program aims to strengthen the capacity of local entrepreneurs in business management and digital marketing to enhance product competitiveness and expand market reach. The implementation method included partner needs identification through observation and interviews, business management training covering simple financial recording, production planning, and resource management, as well as digital marketing training through the use of social media and online marketplaces. These activities were supported by continuous monitoring and mentoring to ensure practical application of the materials. The results indicate an improvement in participants’ ability to manage business administration, enhancement in promotional content quality, and an increase in market reach and digital-based sales transactions. This community service program has a positive impact on strengthening business management practices and fostering sustainable economic empowerment for the Bukit Hijau Village community.